Najnovejše smeri razvoja urbane prenove v Budimpešti - Csanádi, Gábor (Urbani izziv, 2010)
This article outlines recent social processes in central Budapest, focusing on social sustainability and gentrification, and presents the potential social conflicts emerging in this area. We examine the recent history of the housing market and areas of gentrification in the city centre. The second part of the article presents the trends and possible long-term effects of real-estate development in the research area. The article concludes that the gentrification events in central Budapest could be a warning signal of future social displacement and social exclusion.
Keywords: Budapest; Budimpešta; prenova; urbana sociologija; urbanistični načrti; urbanistični razvoj